Penegakan Hukum terhadap Pesawat Militer Asing yang Diterbangkan dari Kapal Induk saat Melintas Alur Laut Kepulauan Indonesia (ALKI) - Ahmad Novam Hajaruman (Faculty of Law Hang Tuah University, 2015)
The Archipelagic Sea Lane Passage of Indonesia is a sea lane on Indonesian waters which can be bypassed by foreign ships and aircrafts continuously, expeditiously and rapidly based on United Nation Convention on the Law Of the Sea, 1982 which Indonesia has ratified through Act Number 17 of 1985. As archipelagic state, Indonesian government has stipulated Act Number 6 of 1996 dated August 8, 1996 on Indonesian Waters. It is executed by Government Regulation Number 37 of 2002 on the Rights and Duties of Foreign Ships and Aircrafts Exercising the Right to Cross the Archipelagic Sea Lane Passage of Indonesia. However, there are still many aircrafts, especially foreign military aircrafts that cross the Archipelagic Sea Lane Passage of Indonesia beyond the existing provisions. Based on the issue, how to regulate the foreign military aircrafts as a unit of aircraft carrier to cross the Archipelagic Sea Lane Passage of Indonesia, and how to punish the foreign military aircrafts passing out of the predetermined route of the Archipelagic Sea Lane Passage of Indonesia. This work is the result of normatively legal research with statute approach and using literature study. Based on the existing provisions above, it can be concluded that the foreign military aircraft flown from the aircraft carrier when they pass the Archipelagic Sea Lane Passage of Indonesia is permitted with condition to comply the existing provisions. If they break rules, they will be warned and can be forcely landed according to existing procedures.